Konsep Desain Kamar Mandi Bertema ”Accessible Restroom” 2007 Analisis Penerapan Konsep ’Desain Universal’ pada Sayembara Perancangan - Yusita Kusumarini; Tri Noviyanto Puji Utomo (Journal of Visual Art and Design, 2008)
Universal design is a design approach which considering that all products, building, exterior and interior spaces be usable to the greatest possible extent by all, regardless of ages and abilities. Given its importance, this approach needs to be promoted and socialized, especially for the design of public facilities (including interior and its complement) in Indonesia. BILiC (Bandung Independent Living Centre) started the assessment for the importance of universal design on public facilities with the 2007 ”Accessible Restroom” international design competition. The presented paper discusses universal design and accessibility in lieu for the evaluation of entry design works of the competition.